Combined application of redox flow battery and DC link in restructured AGC system in the presence of WTS and DSTS in distributed generation unit. Issue 9 (2nd March 2018) - Saha, Arindita; Saikia, Lalit Chandra
Abstract : This article deals with automatic generation control (AGC) of an unequal two‐area system under deregulated environment. Area‐1 comprises distribution generation (DG) and thermal units and area‐2 has gas and thermal units. The DG unit comprises wind turbine system (WTS), dish‐Stirling solar thermal system (DSTS), aqua electrolyser, fuel cell, diesel generator, and battery energy storage system. A maiden attempt has been made to apply a cascade controller called integer order proportional–integral–derivative with filter (PIDN) cascaded with fractional order integral–derivative (PIDN‐FOID) controller and its performance is compared with I, PI, and PIDN controller. Investigation reveals that PIDN‐FOID outperforms in terms of peak deviations, settling time, and oscillations in both constant and variable conditions of wind speed and solar insolation. The effect of using WTS, DSTS, both WTS and DSTS on system dynamics is also evaluated and explored that system dynamics improves with integration of these renewable sources. The gains and other parameters are optimised by whale optimisation algorithm. The effect of DC link, redox flow battery, and both on system dynamics is also evaluated in the presence of PIDN‐FOID controller and explores that the use of these shows promising dynamic performance. The robustness of controller gains and parameters are tested with change in size of contract.